Indole type akuammiline from Vinca erecta: Crystal structure of 10-OAc-Akuammine - Adizov, Shahobiddin; Tashkhodjaev, Bakhodir (European Journal of Chemistry, 2019)
Single crystal X-ray diffraction has established the absolute configuration of the indole alkaloids from Vinca erecta such as akuammiline-o-acyl derivative of akuammine with a 3D stable polycyclic framework. Crystal data for C24H28N2O5: orthorhombic, space group P212121 (no. 19), a = 7.349(3) Å, b = 16.099(5) Å, c = 17.323(5) Å, V = 2049.5(12) Å3, Z = 4, T = 293(2) K, μ(CuKα) = 0.789 mm-1, Dcalc = 1.376 g/cm3, 1742 reflections measured (7.496° ≤ 2Θ ≤ 119.792°), 1742 unique (Rsigma = 0.0374) which were used in all calculations. The final R1 was 0.0608 (I > 2σ(I)) and wR2 was 0.1680 (all data). The polycyclic framework of the well-known picrinine and akuammine is compared. The ether bridges located in different positions of the framework and forming five-membered cycles do not change the conformation of the polycyclic akuammiline framework. In V. erecta alkaloids, the exomethylene fragment (C18-C19=C20-C21) of the polycyclic backbone always takes on the E-condition.